Non-Uniform Temperature Distribution in Multilayer Thermal Protective Coating with Curved Interfaces; Key Engineering Materials; Vol. 685 : High Technology: Research and Applications 2015 (HTRA 2015) - Chumakov Yu. A. Yuri Aleksandrovich (Numerical Simulation of Physical and Chemical Processes, 2016)
Title screen